4-phenyl-5-((pyrimidin-2-ylthio)methyl)-1,2,4-triazole-3-thiol as a platform for the synthesis of unsymmetrical disulfides - Karpenko, Yu. V.; Panasenko, M. O.; Карпенко, Юрій Вікторович; Панасенко, Марія Олександрівна (Запорізький державний медико-фармацевтичний університет, 2025)
The aim of the work is to develop a method for the synthesis of unsymmetrical disulfides of 4-phenyl-5-((pyrimidin-2-ylthio)methyl)-1,2,4- triazole-3-thiols under mild conditions, with high selectivity and wide tolerance to functional groups, including the disulfide fragment as a promising structural framework for the development of new active pharmaceutical ingredients. Materials and methods. 1H NMR spectra were recorded on a Bruker AC-500 spectrometer (500 MHz) in DMSO-d6. Elemental analysis (C, H, N, S) was performed using an ELEMENTAR vario EL cube. Melting points were determined using the capillary method. Results. A new strategy for the synthesis of unsymmetrical disulfides of 4-phenyl-5-((pyrimidin-2-ylthio)methyl)-1,2,4-triazole-3-thiols using 1-chlorobenzotriazole has been developed, providing high product yields and selective transformation. This method does not require low temperatures and demonstrates high compatibility with various functional groups, allowing easy modification of molecules and further research potential. Spectral data confirm the structure of the obtained compounds and indicate the formation of stable disulfide bonds. Conclusions. The synthesis of new unsymmetrical disulfides of 4-phenyl-5-((pyrimidin-2-ylthio)methyl)-1,2,4-triazole-3-thiols was successfully carried out under mild conditions using 1-chlorobenzotriazole as a selective reagent, resulting in high yields and good tolerance to functional groups. Their structural similarity to natural antioxidants such as cystine and allicin makes them promising model compounds for further studies of the mechanisms of redox activity and the development of new drugs to regulate oxidative stress. Мета роботи – розробка методу синтезу несиметричних дисульфідів 4-феніл-5-((піримідин-2-ілтіо)метил)-1,2,4-тріазол-3-тіолів за м’яких умов із високою селективністю та широкою толерантністю до функціональних груп, включаючи дисульфідний фрагмент як перспективний структурний каркас для розроблення нових активних фармацевтичних інгредієнтів. Матеріали і методи. Спектри 1H ЯМР записано на спектрометрі Bruker AC-500 (500 МГц відповідно) у ДМСО-d6. Елементний аналіз (C, H, N, S) здійснили на приладі ELEMENTAR vario EL cube. Температури плавлення визначали капілярним методом. Результати. Розроблено нову стратегію синтезу несиметричних дисульфідів 4-феніл-5-((піримідин-2-ілтіо)метил)-1,2,4-тріазол-3-тіолів за допомогою 1-хлоробензотріазолу, що забезпечує високий вихід продуктів і селективність перетворення. Цей метод не потребує низьких температур і характеризується високою сумісністю з різноманітними функціональними групами, що дає змогу легко модифікувати молекули, підвищує їхній потенціал для наступних досліджень. Спектральні дані підтверджують структуру отриманих сполук і вказують на утворення стабільних дисульфідних зв’язків. Висновки. Синтез нових несиметричних дисульфідів 4-феніл-5-((піримідин-2-ілтіо)метил)-1,2,4-тріазол-3-тіолів успішно здійснено за м’яких умов із використанням 1-хлоробензотріазолу як селективного реагенту, що забезпечує високий вихід і значну толерантність до функціональних груп. Структурна подібність до природних антиоксидантів, зокрема цистину й аліцину, робить їх перспективними модельними сполуками для наступних досліджень механізмів окисно-відновної активності та розроблення нових препаратів, спрямованих на регуляцію оксидативного стресу.
4-феніл-5-((піримідин-2-ілтіо)метил)-1,2,4-тріазол-3-тіол як платформа для синтезу несиметричних дисульфідів
Keywords: 1,2,4-triazole; disulfides; mild conditions; high selectivity; antimicrobial activity; antioxidant activity; 1,2,4-тріазол; несиметричні дисульфіди; м’які умови; висока селективність; протимікробна активність; антиоксидантна активність